Workplace writing in L2 experiences among millennial workforce: learning to write in English - Nurul Kamalia Yusuf,; Melor Md Yunus,; Mohamed Amin Embi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The challenges confronted by the Millennial workforce across the transition from higher education to workplaces are well acknowledged globally. Institutions of higher learning (IHLs) have a responsibility to prepare graduates to become a functional workforce. Among the real-world skills to be taught is workplace writing, which is fundamental in work organizations. This paper aims to explore learning to write in English for the workplace as experienced by millennial workforces. A descriptive phenomenological research design was employed in order to gain an in-depth understanding of the Millennial workforce’s lived experiences in workplace writing. Seven of them were selected based on a set of criteria. A two-tiered method of interviews was employed to establish the context, relay specific details of the participants’ experience and contemplate the meaning of their experiences. In addition, self-portrait descriptions were used to triangulate the data. The findings revealed that the millennials experienced both learning for and about workplace writing in both settings: IHLs and workplaces. They further revealed the practicality of English writing and business writing courses they had taken at IHLs. They have also experienced learning at their workplace through participating in trainings, social interaction, first-hand experiences and intrinsic motivation. These findings can be used as an instructional guideline for ESL workplace writing courses in IHLs. The appropriate instructions and contents could be convenient not only to improve teaching and learning but also promote a more meaningful learning to the graduating students which in turn, creates a powerful workforce who is able to command by today’s workplace standards.